Challenges encountered by critical care unit managers in the large intensive care units - Mokgadi C. Matlakala; Martie C. Bezuidenhout; Annali D.H. Botha (AOSIS, 2014)
Background: Nurses in intensive care units (ICUs) are exposed regularly to huge demands interms of fulfilling the many roles that are placed upon them. Unit managers, in particular, are responsible for the efficient management of the units and have the responsibilities of planning, organising, leading and controlling the daily activities in order to facilitate the achievement of the unit objectives. Objectives: The objective of this study was to explore and present the challenges encountered by ICU managers in the management of large ICUs. Method: A qualitative, exploratory and descriptive study was conducted at five hospital ICUs in Gauteng province, South Africa. Data were collected through individual interviews from purposively-selected critical care unit managers, then analysed using the matic coding. Results: Five themes emerged from the data: challenges related to the layout and structure of the unit, human resources provision and staffing, provision of material resources, stressors in the unit and visitors in the ICU. Conclusion: Unit managers in large ICUs face multifaceted challenges which include the demand for efficient and sufficient specialised nurses; lack of or inadequate equipment that goes along with technology in ICU and supplies; and stressors in the ICU that limit the efficiency to plan, organise, lead and control the daily activities in the unit. The challenges identified call for multiple strategies to assist in the efficient management of large ICUs.